Energy Drinks Consumption among Iranian University Students and Associated Factors - Goli 1, Shahrbanoo; Zarei 2, Fatemeh; Akbarzadeh 2, Isa; Rezaei 2, Nilay; Jafar 2, Mohammad Reza; Mirrezaie 3, Naeemeh; Mirrezaie 4*, Seyed Mohammad (Shahroud Journal of Medical Sciences, 2019)
Background & Aims: There is no study in Iran about the Energy drinks (EDs) use by students. The purpose of this study was to evaluate the prevalence of EDs consumption and its related factors among the students. Methods:This cross-sectional study carried out among students of Shahroud University of Medical Sciences. Using a standardized, pretested and self-administered questionnaire, the data were collected. The questionnaire consisted of 65 questions that asked the students' sociodemographic characteristics and their knowledge and habits of ED consumptions. Results:Of all participants 66.3% were female, 63.1% of students live in dormitories and 6.9% and 19.9% of them live with friends and parents, respectively. Almost 11.5 percent of students are user of energy drinks. The most common reason to try an ED was ‘‘its special tastes’’ (36.2%), followed in order of frequency by ‘‘to stay awake for long hours’’. Logistic regression modeling of EDs use indicated that, male gender, students who live alone and higher monthly costs for personal requirements were also positively and significantly associated with EDs use. Conclusions:Despite thelow prevalence of EDs consumption in our study samples,male students, living alone and higher monthly costs for personal requirements are factors associated with more EDs consumption. Key words: Energy Drink; Youths; University Students; Iran.